Distant recurrence in a patient with polyp-confined stage IA serous endometrial carcinoma treated with adjuvant chemotherapy: A case report and review of literature - Annalyn Welp; Sarah Temkin; Stephanie Sullivan (Elsevier, 2020)
Uterine serous carcinoma is a rare, high-risk histological subtype of endometrial cancer, and use of adjuvant treatment in early stage IA disease is inconsistent, especially when the tumor is confined entirely within an endometrial polyp. We herein present a case of extrauterine recurrence in a 67-year-old female with polyp-confined, stage IA uterine serous endometrial cancer. She underwent comprehensive surgical staging with the pathology returning a 5 cm uterine serous carcinoma confined completely to a 7 cm polyp with negative margins, negative myometrial and lymphovascular space invasion, and twenty-nine negative para-aortic and pelvic lymph nodes. She went on to complete six cycles of adjuvant carboplatin and paclitaxel. She presented with a new pleural effusion approximately 20 months after receiving definitive treatment, and a diagnosis of recurrent, metastatic uterine serous carcinoma was confirmed through cytology. A review of the literature suggests practice patterns involving adjuvant treatment for polyp-confined stage IA uterine serous carcinoma are highly variable. Prospective studies clarifying the utility of adjuvant treatment for polyp-confined disease in comprehensively staged patients, especially pertaining to the impact this pathology has on recurrence risk, are needed for these patients. Keywords: Uterus, Serous, Metastasis, Adjuvant treatment, Polyp